2011
DOI: 10.1155/2011/529049
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ferrofluid on the Performance and Emission Patterns of a Four-Stroke Diesel Engine

Abstract: Experimental tests were carried out to investigate the effects of adding water-based ferrofluid to diesel fuel in a diesel engine. These effects included the combustion performance and exhaust emission characteristics of the diesel engine. To this end, emulsified diesel fuels of 0, 0.4, and 0.8 ferrofluid/diesel ratios by volume were used in a four-stroke diesel engine, operating at 2200 rpm. The results indicate that adding ferrofluid to diesel fuel has a perceptible effect on engine performance, increasing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 19 publications
2
33
0
Order By: Relevance
“…Based on the above, most of the researchers conducted their experiments with metal nanoadditives [10], metal oxide nanoadditives [11e14], magnetic nano fluid additives [15,16] and water diesel nanoparticle, emulsion [17e19], water diesel carbon nano tube emulsion [20], and nano organic additives [21,22] to the diesel fuel. Very few researchers worked, on the use of nanoadditives to biodiesel for the enhancement of the performance and emission characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above, most of the researchers conducted their experiments with metal nanoadditives [10], metal oxide nanoadditives [11e14], magnetic nano fluid additives [15,16] and water diesel nanoparticle, emulsion [17e19], water diesel carbon nano tube emulsion [20], and nano organic additives [21,22] to the diesel fuel. Very few researchers worked, on the use of nanoadditives to biodiesel for the enhancement of the performance and emission characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Heejung et al (2005) observed that addition of cerium to the diesel brought significant changes in the number-weighted size distributions, light-off temperature and kinetics of oxidation. Shafii et al (2011) studied the effect of ferro-fluid on the performance and emission characteristics of a CI engine. The emulsified diesel fuel and 0.4 and 0.8 ferro-fluid/diesel ratio by volume blends were used in this research.…”
Section: Introductionmentioning
confidence: 99%
“…The complete rig set up is shown in plate (1) and schematically in fig (1). The data acquisition and engine control system is shown in plate (2). The system records the pressure via crank angle diagram (p, ɵ ), engine speed (rpm) and temperature of exhaust gases.…”
Section: Methodsmentioning
confidence: 99%
“…They also reduce UHC and smoke emission and they reduced BSFC to 0.358(kg/kW.hr). [2] investigated experimentally the effect of adding magnetic nanoparticle (10nm) with doses of 0.4 and 0.8 Ferro by volume to the diesel fuel. The tested engine was a 4 stroke, 4 cylinder, 43 kW, water cooled and constant speed (4800 rpm).…”
Section: Introductionmentioning
confidence: 99%